Increased Sebum Excretion in Patients with Breast Cancer. Issue 5697 (14th March 1970) - Burton, J. L.; Cunliffe, W. J.; Shuster, Sam
Abstract : The rate of sebum excretion from the forehead skin of patients with early breast cancer was found to be just significantly higher than in age-matched control women. This may indicate that some breast cancer patients have an increase in circulating or tissue-bound sebotrophic hormones, or a decrease in their inhibitors.